A new species of Epidendrum (Orchidaceae: Laeliinae) of the Incomptum group from the north of Antioquia, Colombia - Rincón González, Milton
A new species of Epidendrum of the Incomptum group is described and illustrated, thus far found only at the type locality. Information is provided to separate the species belonging to the Arbuscula and Incomptum groups. Additionally, the new taxon described herein, Epidendrum pembertonii, is thoroughly compared with the four most morphologically similar species (E. brenesii, E. bisulcatum, E. foldatsii, E. sotoanum), revealing notable differences in the number and shape of leaves, inflorescence length, flower color, venation of sepals, as well as the shape and ornamentation of the lip and column.